PENGARUH VARIASI BASIS GELLING AGENT TERHADAP KARAKTERISTIK FISIK MASKER GEL PEEL-OFF EKSTRAK DAUN PEPAYA (Carica papaya L.) - Sisca Devi (Jurnal Mitra Kesehatan, 2023)
Introduction: Acne is a chronic inflammation of the sebaceous glands due to inflammation and bacterial infection. One of the plants used to treat acne is papaya leaves (Carica papaya L.) because it has alkaloid compounds as antibacterial causes of acne. This study aims to determine the effect of gelling agent base variations on the physical characteristics of peel-off gel mask preparations and to determine the gelling agent base that produces the best physical characteristics of the preparation. Method: The method used was an experimental study using a completely randomized design (CRD) with three treatments and nine repetitions. Variations of the base gelling agent used were gelatin, CMC-Na, and carbopol 940. Each formula was tested for physical characteristics in the form of organoleptic tests, homogeneity, viscosity, spreadability, adhesion, drying time, and pH. Data analysis was carried out by testing for normality and homogeneity with the SPSS program. If the distribution of the resulting data shows normal and homogeneous, then the ANOVA test is used, while if it does not meet the normality and homogeneity requirements, the Kruskal-Wallis test is used with a 95% confidence level. Results: The resulting research shows that variations in the gelling agent gelatin, CMC-Na, and carbopol affect the physical characteristic test of papaya leaf extract peel-off gel masks in the form of pH, viscosity, adhesion, spreadability and drying time. Statistical results show that variations in gelling agents produce significant differences. Conclusion: Variations in gelling agent bases affect the physical characteristics of papaya leaf extract peel-off gel masks (Carica papaya L.) in the form of pH, viscosity, adhesion, spreadability and drying time of preparations. The gelling agent base that produces the best characteristics of papaya leaf extract (Carica papaya L.) peel-off gel mask preparation, namely gelling agent Karbopol 940 in formula 3 because it produces preparations that meet the requirements of all physical characteristic tests.